Factors preventing early case detection for women affected by leprosy: a review of the literature - Victoria Grace Price (Taylor & Francis Group, 2017)
Background: Although leprosy can affect both sexes equally, it is globally reported that men are affected, or simply report, more often than females at the average ratio of 2:1. If cases are simply not being reported, women may be suffering in silence more often than men, and, therefore, understanding the social reasons for this in a number of countries could support the prevention of long-term disabilities caused as a result of leprosy. Objectives: The objective of this review is to recognise the current academic literature surrounding the potential factors for late diagnosis of women affected by leprosy, giving possible explanations for the 2:1 gender disparity observed in case detection globally. It is hoped that health practitioners will become more equipped to recognise these barriers and ensure they are doing whatever possible to encourage women to report the early symptoms of leprosy. Methods: The review used a systematic search process in order to identify gender-related publications using robust research, useful for gleaning a cross-cultural perception of issues women may confront on the prospect of a diagnosis of leprosy. Results: Identifying 12 publications from just five countries, the review found there to be four overarching areas which may be considered barriers more often faced by women: societal stigma; women's dependence and low status; self-stigmatising attitudes; and the gender insensitivity of leprosy services. Conclusion: Stigma surrounding leprosy experienced from these four overarching areas can all be attributed to the later diagnosis of women affected by leprosy, in relation to their male counterparts. The need for future research surrounding the specific experience of women affected by leprosy is pressing.